The proof of instantaneous gravitation - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2022)
According to Newton, the changes in the gravitational field propagate instantaneously. If we examine the earth on its orbit around the sun and assume a light-fast effect of the gravitation, the following situation would occur: Through the sun, a force would not act directly on the earth's center of gravity, but on the point where the earth's center of gravity was 8 minutes ago, and through the earth, a force would not act directly on the sun's center of gravity, but on the point where the sun's center of gravity was 8 minutes ago. This time delay would cause the Sun-Earth distance to build up and the Earth to leave orbit. We would be dealing with unstable orbits of orbiting masses in space. However, this is not observed.It is to be proved that the gravity with 1. the constant product of mass and time duration which passes on it, 2. the time dilation, and 3. the permanent enlargement of stable orbits can be described exactly by the Newton's basic law. Newton would continue to apply and describe gravity physically correct in accordance with observation. As a conclusion, there should be an instantaneous gravitational propagation.